2011
DOI: 10.3390/ma4050857
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Multilayered Diamond Coatings for Biomedical Implants

Abstract: With incredible hardness and excellent wear-resistance, nanocrystalline diamond (NCD) coatings are gaining interest in the biomedical community as articulating surfaces of structural implant devices. The focus of this study was to deposit multilayered diamond coatings of alternating NCD and microcrystalline diamond (MCD) layers on Ti-6Al-4V alloy surfaces using microwave plasma chemical vapor deposition (MPCVD) and validate the multilayer coating’s effect on toughness and adhesion. Multilayer samples were desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…The aim of our present study is to know the suitability of polycrystalline diamond (PCD), if this ceramic coating can be used, for example, in hip prosthesis, instead of existing alumina ceramic. PCD coating on the acetabular cup and femoral head may replace/supplement the existing alumina materials, to prolong the implant life and also may prevent the unnecessary formation of wear debris, as harder PCD coating has very low coefficient of friction and it is chemically inert [8,9]. Biocompatibility and non-toxic effect on cells by PCD surface [10][11][12][13] also are the advantages of choosing diamond coating as a new material for future implants to get rid of the problem of tribo-corrosion [14].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our present study is to know the suitability of polycrystalline diamond (PCD), if this ceramic coating can be used, for example, in hip prosthesis, instead of existing alumina ceramic. PCD coating on the acetabular cup and femoral head may replace/supplement the existing alumina materials, to prolong the implant life and also may prevent the unnecessary formation of wear debris, as harder PCD coating has very low coefficient of friction and it is chemically inert [8,9]. Biocompatibility and non-toxic effect on cells by PCD surface [10][11][12][13] also are the advantages of choosing diamond coating as a new material for future implants to get rid of the problem of tribo-corrosion [14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the long-term durability of the prosthetic joint materials rely on the successful control of both the corrosion that produces ions release and the tribocorrosion resistance that produces ions release and oxide or plastic debris, Physical Vapor Deposition (PVD) multilayer coatings offer a multifunctional protection alternative and good adherence to metallic substrates in comparison to the monolayer coating [15,[21][22][23][24][25][26]. The multilayer combine the properties of different materials in a single protective layer.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on using these deposition techniques on modified diamond and DLC, materials well known for their exceptional resistance to physical wear and chemical corrosion [49,50]. Our study has demonstrated significant neuronal adhesion with cells that maintain their characteristic morphology on both boron-doped diamond and P:DLC.…”
Section: Discussionmentioning
confidence: 99%